Impact of vertical electrokinetic-flushing technology to remove heavy metals and polycyclic aromatic hydrocarbons from contaminated soil - Giannis, Apostolos (2013)
This study presents the feasibility of using the vertical electrokinetic-flushing technology for the simultaneous removal of cadmium (Cd), lead (Pb), zinc (Zn), as well as phenanthrene and pyrene from contaminated soils. Eight vertical bench-scale electrokinetic-flushing experiments were conducted analyzing the effect of treatment duration, initial soil water content and soil type. The highest removal efficiency was achieved for Cd (82%), followed by Zn (73%) and Pb (37%) from natural soil after 8 days of treatment with water content 60%. The study demonstrated that the metals were extracted from the soil mainly due to the dominated low pH conditions and vertically migrated from anode towards the cathode. Besides, it was found that the removal efficiency was increased in the experiments with higher treatment duration, while the higher soil water content further enhances metals removal. In terms of the organic pollutants, under the conditions conducted the electrokinetic-flushing treatment, low removal efficiency for phenanthrene (29%) and pyrene (19%) was achieved. However, it is noticeable that without the use of any solubilizing agent the organic pollutants could be removed following the movement of the pore fluid.